Dicarboxylic Acid Separation by Dynamic and Size‐Matched Recognition in Solution and in the Solid State. (2nd January 2018) - Kumar, Vijith; Pilati, Tullio; Terraneo, Giancarlo; Ciancaleoni, Gianluca; Macchioni, Alceo; Resnati, Giuseppe; Metrangolo, Pierangelo
Abstract: Bis(trimethylammonium) alkane diiodides dynamically encapsulate dicarboxylic acids through intermolecular hydrogen bonds between the I − anions of the hosts and the carboxylic OH groups of the guests. A selective recognition is realized when the size of the I − ⋅⋅⋅HOOC(CH2 /CF2 )n COOH⋅⋅⋅I − superanion matches the dication alkyl chain length. Dynamic recognition is also demonstrated in solution, where the presence of the size‐matching organic salt boosts the acid solubility profile, thus allowing efficient mixture separation.